ЗАВИСИМОСТЬ ДОПОЛНИТЕЛЬНЫХ ПОТЕРЬ В ТРЕХФАЗНЫХ СИСТЕМАХ ЭЛЕКТРОСНАБЖЕНИЯ ОТ РЕАКТИВНОЙ МОЩНОСТИ И ПУЛЬСАЦИЙ МГНОВЕННОЙ АКТИВНОЙ МОЩНОСТИ - Жемеров , Г.Г.; Тугай , Д.В. (Інститут електродинаміки НАН України, Київ, 2015)
Qualified ratio relates the power of additional losses with the reactive power and instantaneous active power pulsations for three-phase three-wire energy supply systems with symmetrical sinusoidal voltage source is obtained. For the verification of this ratio a computer Matlab-model of three-phase energy supply system is created. Basis of the method for detecting the causes of additional losses in the energy supply system by the value of their components are proposed. References 7, table 1, figure 1.